Educated a memoir - Westover, Tara; Whelan, Julia 1984- (New York, NY Random House Audio Westminster, MD, 2018)
Traces the author's experiences as a child born to survivalists in the mountains of Idaho, describing her participation in her family's paranoid stockpiling activities and her resolve to educate herself well enough to earn acceptance into a prestigious university and the unfamiliar world beyond.
Choose the good -- The midwife -- Cream shoes -- Apache women -- Honest dirt -- Shield and buckler -- The Lord will provide -- Tiny harlots -- Perfect in his generations -- Shield of feathers -- Instinct -- Fish eyes -- Silence in the churches -- My feet no longer touch Earth -- No more a child -- Disloyal man, disobedient heaven -- To keep it holy -- Blood and feathers -- In the beginning -- Recitals of the fathers -- Skullcap -- What we whispered and what we screamed -- I'm from Idaho -- A knight, errant -- The work of sulphur -- Waiting for moving water -- If I were a woman -- Pygmalion -- Graduation -- The hand of the almighty -- Tragedy then farce -- A brawling woman in a wide house -- Sorcery of physics -- The substance of things -- West of the sun -- Four long arms, whirling -- Gambling for redemption -- Family -- Watching the buffalo -- Educated.
Title from container.
Compact disc.
Read by Julia Whelan.
107190
Keywords: Westover, Tara -- Family; Women -- Idaho -- Biography; Survivalism -- Idaho -- Biography; Home schooling -- Idaho -- Anecdotes; Women college students -- United States -- Biography; Victims of family violence -- Idaho -- Biography; Subculture -- Idaho; Christian biography; Biography & Autobiography -- Women; Biography & Autobiography -- Religious; Biography & Autobiography -- Personal Memoirs; Idaho -- Rural conditions -- Anecdotes; Idaho -- Biography; Audiobooks; Idaho -- Biography; Autobiographies; Biography; Anecdotes; Christian biography